Use of Computed Tomography in Evaluation and Management of Shell Fracture in a Red Eared Slider Turtle ( Trachemys scripta elegans) A Case report - Velavan, A.; Dhaarani, G; Ayyappan, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Traumatic lesions of the shell are common problems in chelonians. Lesions of the shell vary in severity from a simple superficial abrasion (with a loss of the external skin layer and exposure of the bone) to complicated fractures of the carapace with exposure of internal organs of the coelom and injury of the soft tissues (Barten, 2006). In most shell or skeletal injuries in the turtle, plain radiographic data do not reveal the extent of complex fractures due to superimposed bone structures (Abou-Madi et al., 2002). In Comparison  with conventional radiography, computed tomography (CT) allows better distinction of specific tissue densities and discrete changes in organ size, shape, margin, contour and position (Gaudron et al., 2001). Computed tomography is a non-invasive, cross-sectional diagnostic imaging technique that offers significant advantages for detection of pathologies in chelonians, and is ideal for diagnosing skeletal and soft tissue abnormalities (Gumpenberger and Henninger, 2001). The aim of the present work was to evaluate the three dimensional computed tomography (CT)  for clinical examination of shell lesions in a red eared slider turtle.
Keywords: Tomography; Evaluation; Management; Red Eared Slider Turtle